ANALISIS DRAMATURGI BANYOLAN KARTOLO EPISODE SETORAN DI JTVSURABAYA - Wangi, Mega Pandan; P, Basnendar H (Capture : Jurnal Seni Media Rekam, 2012)
This study is based on the curiosity of the author regarding of aspects of thecharacterizations contained in the program JTV Surabaya namedBanyolan Kartolo (Kartolo Jokes),especially the episode 273 with the titleâ€œSetoranâ€.The study focused on the art of dramaturgyand the division of roles on the player.This study uses a qualitative research especially thefenomenology approach.With this approach disclosed to any phenomenon that occurs in theproduction of Kartolo Jokes. Data were analyzed using an interactive model, namely datareduction,data presentation,and then draw conclusions.The results of this study indicate thatthe elements that exist in Ludruk characterization Kartolo Jokes.In the jokes only use three typesof roles which the protagonist,antagonist and extras.Supporting element is the script,directors,steering studio, production assistants, camera person, lights man, sound engineers, and artisticdirector.Keywords:Ludruk,BanyolanKartolo,JTV Surabaya,and Dramaturgy